A Comparative Evaluation of Wound Healing Activity of Various Parts of Clerodendrum infortunatum Linn. - Kumar, Praveen; Tripathi, Laxmi (Asian Journal of Chemistry, 2013)
In light of the traditional claims and experimental evidences to use Clerodendrum infortunatum Linn. in the treatment of wounds, an investigation was carried out to compare the wound healing activity of methanolic extract of leaves, roots and whole plant of C. infortunatum L. The wound healing activity was evaluated using excision, incision and dead space wound models and acute toxicity study was also performed. The study demonstrated a significant increase in the wound healing activity of the methanolic extract of leaves, roots and whole plant of C. infortunatum compared with those who received the placebo control treatments. Wound contraction, increased tensile strength and increased hydroxyproline content support the above findings. Among the three extracts the methanolic extract of leaves showed most potent wound healing activity, followed by extract of whole plant and roots.